NMR Assessment of Therapeutic Peptides and Proteins: Correlations That Reveal Interactions and Motions. (24th October 2019) - Falk, Bradley T.; Liang, Yingkai; Bailly, Marc; Raoufi, Fahimeh; Kekec, Ahmet; Pissarnitski, Dmitri; Feng, Dennis; Yan, Lin; Lin, Songnian; Fayadat‐Dilman, Laurence; McCoy, Mark A.
Abstract: NMR measurements of rotational and translational diffusion are used to characterize the solution behavior of a wide variety of therapeutic proteins and peptides. The timescales of motions sampled in these experiments reveal complicated intrinsic solution behavior such as flexibility, that is central to function, as well as self‐interactions, stress‐induced conformational changes and other critical attributes that can be discovery and development liabilities. Trends from proton transverse relaxation ( R 2 ) and hydrodynamic radius ( R h ) are correlated and used to identify and differentiate intermolecular from intramolecular interactions. In this study, peptide behavior is consistent with complicated multimer self‐assembly, while multi‐domain protein behavior is dominated by intramolecular interactions. These observations are supplemented by simulations that include effects from slow transient interactions and rapid internal motions. R 2 – R h correlations provide a means to profile protein motions as well as interactions. The approach is completely general and can be applied to therapeutic and target protein characterization. Abstract : Simple NMR relaxation and diffusion measurements allows us to characterize the solution behavior of therapeutic peptides and proteins. Trends in R 2 / R h differentiate between various intermolecular and intramolecular interactions as well as motions on different timescales.